Enhancing Supply Chain Performance Analysis Through Methodological Integration: A SCOR-Based Framework with AHP and Fishbone Application - Aprillia, Ferlita; Nahum Marpaung, Jonathan (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study presents a structured framework for supply chain performance evaluation by integrating the SCOR model with the Analytical Hierarchy Process (AHP) and Fishbone Diagram. The approach is applied to PT. XYZ, an Indonesian pharmaceutical company recently entering the medical device distribution sector. The objective is to demonstrate how combining these methods can enhance the accuracy and depth of supply chain diagnostics. SCOR Level 1 identifies performance gaps, AHP in Level 2 prioritizes improvement areas, and Fishbone in Level 3 explores root causes. Rather than focusing solely on outcome metrics, the study emphasizes how method integration enables clearer identification of performance issues and actionable priorities. Results indicate that reliability, responsiveness, and agility are the most pressing concerns, primarily due to workforce limitations, digitalization gaps, and planning inefficiencies. This integrated approach provides deeper insights, better alignment between strategy and operations, and more targeted recommendations. It offers a practical and replicable model for organizations operating in highly regulated or transitional industries.